The Impact of High Performance Work Systems (HPWS) on Employee Performance through Employee Empowerment as Mediation - Guritno, Bambang; Widagdo, C Susmono; Nugraheni, Krisnawati Setyaningrum (JURNAL ILMIAH EDUNOMIKA, 2024)
Fierce competition and globalization require organizations to innovate in improving performance, which becomes a priority goal for companies. High Performance Work Systems (HPWS) adopted by companies can enhance employees' skills, motivation, and engagement. Empowerment is considered a positive aspect that must be fulfilled in work and has several characteristics marked by vigor, dedication, and absorption. The urgency of this research is to bridge the gap by investigating the interaction between HPWS, employee empowerment, well-being, and employee performance in academic literature with HPWS designed and implemented in practice. This study aims to investigate and explain theoretically and empirically the impact of HPWS on employee performance through employee empowerment as a mediator. This research will contribute to the field of organizational and management studies and attempt to explain the relationship between HPWS and employee performance. This study uses a quantitative method which is explanatory research that refers to the hypothesis to be tested against the occurring phenomena. This research is analyzed using the Structural Equation Model (SEM) technique with Partial Least Square (PLS) as a tool to process the technique. HPWS (High Performance Work Systems) has a positive and significant effect on employee performance. This shows that the effective implementation of HPWS can directly improve employee performance. HPWS has a positive and significant effect on employee empowerment. The HPWS system implemented by the company has successfully created a supportive work environment and empowered employees. Employee empowerment has a positive and significant effect on employee performance. A high level of empowerment in employees is proven to significantly improve their performance. Employee empowerment mediates the relationship between HPWS and employee performance.